An Environmentally Stable and Lead‐Free Chalcogenide Perovskite. (24th April 2020) - Gupta, Tushar; Ghoshal, Debjit; Yoshimura, Anthony; Basu, Swastik; Chow, Philippe K.; Lakhnot, Aniruddha S.; Pandey, Juhi; Warrender, Jeffrey M.; Efstathiadis, Harry; Soni, Ajay; Osei‐Agyemang, Eric; Balasubramanian, Ganesh; et al.
Abstract: Organic–inorganic halide perovskites are intrinsically unstable when exposed to moisture and/or light. Additionally, the presence of lead in many perovskites raises toxicity concerns. Herein, a thin film of barium zirconium sulfide (BaZrS3 ), a lead‐free chalcogenide perovskite, is reported. Photoluminescence and X‐ray diffraction measurements show that BaZrS3 is far more stable than methylammonium lead iodide (MAPbI3 ) in moist environments. Moisture‐ and light‐induced degradations in BaZrS3 and MAPbI3 are compared by using simulations and calculations based on density functional theory. The simulations reveal drastically slower degradation in BaZrS3 due to two factors—weak interaction with water and very low rates of ion migration. BaZrS3 photodetecting devices with photoresponsivity of ≈46.5 mA W −1 are also reported. The devices retain ≈60% of their initial photoresponse after 4 weeks under ambient conditions. Similar MAPbI3 devices degrade rapidly and show a ≈95% decrease in photoresponsivity in just 4 days. The findings establish the superior stability of BaZrS3 and strengthen the case for its use in optoelectronics. New possibilities for thermoelectric energy conversion using these materials are also demonstrated. Abstract : Lead‐based halide perovskites are toxic and exhibit poor environmental stability. Herein, a thin‐film and optoelectronic device consisting of barium zirconium sulfide (BaZrS3 )—a lead‐free chalcogenide perovskite—are reported. Experiments and simulations demonstrate that BaZrS3 is intrinsically more stable than organic–inorganic halide perovskites such as methylammonium lead iodide. The findings highlight the potential of chalcogenide perovskites for optoelectronic and thermoelectric applications.